A survey on reputation systems for artificial societies - Tina Balke; Stefan König; Torsten Eymann (Universität Bayreuth, Lehrstuhl für Wirtschaftsinformatik, 2009)
The Internet has caused a revolution in trading. Especially cheap items are now easy to buy and sell on the Internet. As a consequence, sellers nowadays offer a wide range of products on the web, creating an abundance of choice for consumers. Consumers have the opportunity to browse on different auction sites for the item they really want. Along with this success story, however, came the stories of people being cheated by fraudulent online sellers. These frauds cover a range from not delivering what has been promised, the overrating of a product's condition, to deliberate acts of theft. They are a result of so-called asymmetric information. Trust and reputation mechanisms are intended to address this asymmetric information distribution. This article surveys the most common trust and reputation systems.
urn:nbn:de:bvb:703-opus-6169
Keywords: 330; Vertrauen; Electronic Commerce; Computersicherheit